Experimental investigation of packed-bed cross-flow humidifier. (5th May 2017) - Sharqawy, Mostafa H.; Al-Shalawi, Ibrahim; Antar, Mohamed A.; Zubair, Syed M.
Highlights: The performance of a cross-flow packed-bed humidifier is presented. Capacity, saturation efficiency, and specific energy consumption are calculated. The specific energy consumption is almost constant for the same packing material. Effectiveness-NTU model is adopted to estimate the effectiveness of the humidifier. Abstract: This paper presents the experimental performance of a cross-flow packed-bed humidifier. In this humidifier, hot water is sprayed over packing material where air flows though it in a cross flow arrangement. The air is heated and humidified while flowing through the humidifier duct. The humidification capacity, saturation efficiency, and specific energy consumption are calculated using the experimental data of the inlet and outlet conditions for both air and water streams. The variation of these performance indicators with the mass flow rate ratio of water-to-air, the water inlet temperature, and the packing volume; is investigated. It was found that the specific energy consumption is almost constant with variation of the mass flow rate ratio, packing thickness, and water inlet temperature within the investigated range of these parameters. An effectiveness model originally developed for cross-flow packed-bed cooling tower is adopted to estimate the effectiveness of the humidifier. In addition, the effectiveness and the number of transfer units of the humidifier are determined using the experimental data. The model was found to be in a good agreement with the experimental measurement at high capacity ratio with a deviation of 6%. However, the model underestimates the effectiveness at lower capacity ratio with a maximum deviation of 30%.